Mutual effects between aromatic amino acids and guanosine upon vitamin B2 photosensitization in the presence of visible light - Montaña, Maria Paulina (2013)
Considering the importance of the visible-light-induced photodynamic effect in complex bioenvironments, mutual effects between the individual aromatic amino acids (AAs) tyrosine (Tyr), tryptophan (Trp), and histidine (His) and the nucleoside guanosine (GUO) were investigated in pH 7 aqueous solution with vitamin B2 (riboflavin (Rf)) as a dye sensitizer. The quantum yields of oxygen uptake (Φ-O2) for most of the AA−GUO mixtures studied, taken as a measure of overall photooxidation susceptibility, are not straightforwardly predictable from the individual behaviour of the components of the mixture. The final result depends on several connected factors, such as the respective abilities of the substrates as quenchers of the long-lived Rf triplet excited state and the generated reactive oxygen species singlet molecular oxygen (O2(1Δg)) and superoxide radical anion O2?-). A mechanistic interpretation of the Rf-sensitized results can be roughly resumed as follows: Tyr at pH 7 exerts a protective effect on the photooxidation of the mixture Tyr−GUO due to the O2(1Δg) physical quenching by the AA. The same effect was observed for Trp−GUO and His−GUO at pH 7. In these cases, it is attributed to the quenching of 3Rf* by GUO in detriment of the Type II route. For the system Tyr−GUO at pH 9, a marked decrease in the Φ-O2 occurred for the mixture as compared with the respective Φ-O2 for the individual components. It was ascribed to the participation of a radical-mediated mechanism without oxygen consumption in a competitive pathway with the superoxide radical anionmediated route.